Assessment of Self-Regulatory Code Violations in Brazilian Television Beer Advertisements - Vendrame, Alan (Rutgers University, 2010)
OBJECTIVE: Research suggests that alcoholic beverage advertisements may have an adverse effect on teenagers and young adults, owing to their vulnerability to suggestive message content. This study was designed to evaluate perceived violations of the content guidelines of the Brazilian alcohol marketing self-regulation code, based on ratings of the five most popular beer advertisements broadcast on television in the summer of 2005–2006 and during the 2006 FIFA (Fédération Internationale de Football Association) World Cup games. METHOD: Five beer advertisements were selected from a previous study showing that they were perceived to be highly appealing to a sample of Brazilian teenagers. These advertisements were evaluated by a sample of Brazilian high school students using a rating procedure designed to measure the content of alcohol advertisements covered in industry self-regulation codes. RESULTS: All five advertisements were found to violate multiple guidelines of the Brazilian code of marketing self-regulation. The advertisement with the greatest number of violations was Antarctica's “Male Repellent,” which was perceived to violate 11 of the 16 guidelines in the code. Two advertisements had nine violations, and one had eight. The guidelines most likely to be violated by these advertisements were Guideline 1, which is aimed at protecting children and teenagers, and Guideline 2, which prohibits content encouraging excessive and irresponsible alcoholic beverage consumption. CONCLUSIONS: The five beer advertisements rated as most appealing to Brazilian teenagers were perceived by a sample of the same population to have violated numerous principles of the Brazilian self-regulation code governing the marketing of alcoholic beverages. Because of these numerous perceived code violations, it now seems important for regulatory authorities to submit industry marketing content to more systematic evaluation by young people and public health experts and for researchers to focus more on the ways in which alcohol advertising influences early onset of drinking and excessive alcohol consumption.